2006
DOI: 10.1152/ajpgi.00563.2005
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression proteomics of human colon cancer

Abstract: The focus of this study was to use differential protein expression to investigate operative pathways in early stages of human colon cancer. Colorectal cancer represents an ideal model system to study the development and progression of human tumors, and the proteomic approach avoids overlooking posttranslational modifications not detected by microarray analyses and the limited correlation between transcript and protein levels. Colon cancer samples, confined to the intestinal wall, were analyzed by expression pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 82 publications
(76 reference statements)
4
66
1
Order By: Relevance
“…This clearly indicates a high dependence of cancer cells on anaerobic breakdown of pyruvate. In particular, high lactate dehydrogenase 5 activity and resulting effective conversion of pyruvate to lactate have been identified in colon cancer (24,25). Active glycolysis also increases the cytosolic NADH/NAD + ratio and thereby accelerates the activity of lactate dehydrogenase (26).…”
Section: Resultsmentioning
confidence: 99%
“…This clearly indicates a high dependence of cancer cells on anaerobic breakdown of pyruvate. In particular, high lactate dehydrogenase 5 activity and resulting effective conversion of pyruvate to lactate have been identified in colon cancer (24,25). Active glycolysis also increases the cytosolic NADH/NAD + ratio and thereby accelerates the activity of lactate dehydrogenase (26).…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial impairment is often seen in clear cell renal carcinomas (86). In colorectal cancers, transcriptome and proteome analyses have observed that expression of glycolytic and tricarboxylic acid cycle proteins were inversely proportional (87)(88)(89). Also, in breast cancer, the metabolic proteome undergoes a pronounced shift toward an enhanced glycolytic phenotype concurrent with a profound reduction in the F1-ATPase levels with a classification sensitivity of approximately 97% to overall and disease-free survival (90).…”
Section: Mitochondrial Defectsmentioning
confidence: 99%
“…Using the DeCyder software, spots were matched on an intragel basis with differential image analysis (DIA) (5) and on an intergel basis with biological variation analysis (BVA) to assess biological variation (6). Significant spots (⌬fold dependent on statistical power) were selected for robotic excision (7) and digested by trypsin (8), and the peptides were separated by reverse-phase (RP) chromatography and detected by tandem mass spectrometry (9). MS 2 spectra were searched using SEQUEST (10), and identified proteins were imported to MetaCore to search for relevant networks (11).…”
Section: Fig 1 Experimental Designmentioning
confidence: 99%